Mesoporous Silica Particles Integrated with All‐Inorganic CsPbBr3 Perovskite Quantum‐Dot Nanocomposites (MP‐PQDs) with High Stability and Wide Color Gamut Used for Backlight Display. Issue 28 (30th May 2016) - Wang, Hung‐Chia; Lin, Shin‐Ying; Tang, An‐Cih; Singh, Bheeshma Pratap; Tong, Hung‐Chun; Chen, Ching‐Yi; Lee, Yu‐Chun; Tsai, Tzong‐Liang; Liu, Ru‐Shi
Abstract: All‐inorganic CsPbX3 (X=I, Br, Cl) perovskite quantum dots (PQDs) have been investigated because of their optical properties, such as tunable wavelength, narrow band, and high quantum efficiency. These features have been used in light emitting diode (LED) devices. LED on‐chip fabrication uses mixed green and red quantum dots with silicone gel. However, the ion‐exchange effect widens the narrow emission spectrum. Quantum dots cannot be mixed because of anion exchange. We address this issue with a mesoporous PQD nanocomposite that can prevent ion exchange and increase stability. We mixed green quantum‐dot‐containing mesoporous silica nanocomposites with red PQDs, which can prevent the anion‐exchange effect and increase thermal and photo stability. We applied the new PQD‐based LEDs for backlight displays. We also used PQDs in an on‐chip LED device. Our white LED device for backlight display passed through a color filter with an NTSC value of 113 % and Rec. 2020 of 85 %. Abstract : Points of light : Green CsPbBr3 perovskite quantum dots (PQDs), embedded in mesoporous silica (MP), were mixed with red CsPb(Br0.4 I0.6 )3 quantum dots in a silicone resin and placed on an InGaN blue chip. The green and red QDs were excited by blue light with λ=450 nm. The resulting PQD white light emitting diode (LED) exhibits a wide color gamut because of its narrow emission wavelength.